Assessing The Success Factors For Enhancing Product Development - Loon, Mooi Phei (2011)
The main purpose of this research study is to examine the relationship between product development enhancement key areas and the success of product development in one of Japanese producers in moulding company industry. The study here addresses the success of product development in the measurement of time to achieve product qualification success in research and development centre.